THE ROLE OF CONSUMER ATTITUDE IN MEDIATING THE EFFECT OF PRICE PERCEPTION AND FOOD SAFETY CONCERN ON PURCHASE INTENTION OF HEALTHY FOOD (A Study on Cafe Loka Consumers in Gianyar Regency) - Ni Putu Rachel Arisetya Minervani; I Putu Gde Sukaatmadja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The growing trend of a healthy lifestyle has led many people around the world to adopt healthier eating habits. Amidst the increasingly intense competition in the culinary industry, Café Loka has positioned itself as a dining destination offering healthy food as its main menu attraction. This study aims to explain the mediating role of consumer attitude in the relationship between price perception and food safety concern toward purchase intention of healthy food. The research was conducted in Gianyar Regency with a sample of 112 respondents, using questionnaires distributed offline. The sample was selected using purposive sampling. The data were analyzed using path analysis with SPSS 25.0. The results showed that price perception has a negative and significant effect on purchase intention, while food safety concern has a positive and significant effect on purchase intention. Both price perception and food safety concern also have a positive and significant effect on consumer attitude, and consumer attitude positively and significantly affects purchase intention. Moreover, consumer attitude mediates the effect of price perception and food safety concern on purchase intention. The implication of this research is that Café Loka needs to strengthen consumers’ positive perception of pricing and maintain the quality of healthy food offered in order to shape positive consumer attitudes and encourage purchase intention.